Comparative radiopacity of four lowviscosity composites - Micheli Tavares Imperiano; Helen Jamil Khoury; Maria Luiza Anjos Pontual; Marcos Antonio Japiassú Resende Montes; Márcia Maria Fonseca Silveira (Universidade Estadual de Campinas, 2016)
The aim of this study was to evaluate the radiopacity of four commercially available low-viscosity composites. The lowviscosity composites used in this study were Natural Flow, Flow It, Filtek Flow and Protect Liner F. Five specimens of each material were made in stainless-steel ring moulds of 10 mm diameter and 2 mm height. One specimen of each material and a 10-step aluminium wedge were radiographed in an occlusal film. The reading of the optical density was performed in five different locations in each radiographed specimen. The net optical density was calculated, and then the mean values were obtained, and related with the equivalent thickness of aluminium. The radiopacities of each composite, in millimeters of aluminium were: Flow It (3.24 ± 0.17); Filtek Flow (2.25 ± 0.17); Natural Flow (1.50 ± 0.13); Protect Liner F (<1 mm/Al). Flow It and Filtek Flow presented an acceptable radiopacity according to the ISO Standard 4049. Natural Flow and Protect Liner F did not supply the requirements for radiopacity, thus, these materials could be confounded with secondary caries in some clinical applications, such as restorations or cavity lining.